The Relevance of Teachers' Practical Knowledge in the Development of Teacher Education Programs - Débora Izé Balsemão Oss (Universidad Nacional de Colombia, 2018)
Teacher education programs have evolved mostly from the scholarly world's perspective, which can eventually impact the work that practitioners face on an everyday basis, particularly in regard to dealing with their students. This article of reflection addresses aspects related to a Brazilian teacher's personal practical knowledge and the role of practitioners' expertise in dealing with adolescent students (6th to 9th graders). It advocates that teachers' personal practical knowledge is likely to evolve into professional knowledge provided that it is analyzed, verified, and improved. Insights from second language teacher education, reflexive thoughts, and projects developed by the author illustrate what can be considered when developing strategies that are consistent with the envisioned teacher education programs.